Association of race and ethnicity in the receipt of regional anesthesia following mastectomy. Issue 2 (10th November 2020) - Beletsky, Alexander; Burton, Brittany Nicole; Finneran IV, John J; Alexander, Brenton S; Macias, Alvaro; Gabriel, Rodney Allanigue
Abstract : Background: Regional anesthetic techniques have become increasingly used for the purpose of pain management following mastectomy. Although a variety of beneficial techniques have been described, the delivery of regional anesthesia following mastectomy has yet to be examined for racial or ethnic disparities. We aimed to examine the association of race and ethnicity on the delivery of regional anesthesia in patients undergoing surgical mastectomy using a large national database. Methods: We used the American College of Surgeons–National Surgical Quality Improvement Program database to identify adult patients aged ≥18 years old who underwent mastectomy from 2014 to 2016. We reported unadjusted estimates of regional anesthesia accordingly to race and ethnicity and examined differences in sociodemographic characteristics and health status. Multivariable logistic regression was used to report the association of race and ethnicity with use of regional anesthesia. Results: A total of 81 345 patients who underwent mastectomy were included, 14 887 (18.3%) of whom underwent regional anesthesia. The unadjusted rate of use of regional anesthesia was 18.9% for white patients, 16.8% for black patients, 15.6% for Asian patients, 16.5% for Native Hawaiian/Pacific Islander patients, 17.8% for American Indian or Alaska Native and 17.4% for unknown race (p<0.001). With respect to ethnicity, the unadjusted rate of regional anesthesia use was 18.4% for non-Hispanic patients vs 16.1% for Hispanic patients vs 18.6% for the unknown ethnicity cohort (p<0.001). On multivariable logistic regression analysis, the odds of receipt of regional anesthesia was 12% lower in black patients and 21% lower in Asian patients compared with white patients (p<0.001). The odds of regional anesthesia use were 13% lower in Hispanic compared with non-Hispanic patients (p<0.001). Conclusion: Black and Asian patients had lower odds of undergoing regional anesthesia following mastectomy compared with white counterparts. In addition, Hispanic patients had lower odds of undergoing regional anesthesia than non-Hispanic counterparts. These differences underlie the importance of working to deliver equitable healthcare irrespective of race or ethnicity.